DETERMINAN PERILAKU PENCEGAHAN KARIES GIGI SISWA SEKOLAH DASAR DI KOTA SEMARANG - Hermien Nugraheni; Sadimin Sadimin; Sukini Sukini (Jurnal Kesehatan Gigi, 2019)
The results of the  Riskesdas 2018 state that 93% of children in the age range of 5-6 years get cavities. This can affect the nutritional status of children because cavities make children refuse to eat. The cause of Indonesian child cavities can be triggered by various things related to the dental caries preventive behavior. The purpose of this study is to determine the determinants of dental caries preventive behavior in school-aged children.This study was an observational study with a cross-sectional analytic design to see the influence of the habit of brushing teeth, cariogenic food eating habits, the habit of changing toothbrush regularly, routine dental check-up to dental caries in elementary school students.The results of the bivariate analysis revealed that variable habit of brushing teeth with dental caries had an OR of 1.3, variable of how to brush teeth with dental caries had an OR of 1.5, the variable cariogenic food eating habits with dental caries had an OR of 1.2 and variable of cleanliness teeth and mouth with dental caries has an OR of 1.7. There is no significant relationship between the variables studied with dental caries where the value of p 0.05. Based on the results of these studies it is recommended that information and education be provided to elementary school students regarding the correct habits and ways of brushing their teeth and the dangers of eating cariogenic foods.